Odpowiedzi

Najlepsza Odpowiedź!
2009-12-15T19:18:44+01:00
A) 3x=12 /:3
x-y=5

x=4
x-y=5

x=4
4-y=5

x=4
-y=5-4

x=4
-y=1 I*(-1)

x=4
y=-1

b) 5y=2/:5
x+y=2i2/5

y=2/5
x+y=2 2/5

y=2/5
x+2/5=2 2/5

y=2/5
x=2 2/5-2/5

y=2/5
x=2

c) 3m+n=9 /*5
2m-5n=-11

15m+5n=45
2m-5n=-11

17m=34 /:17
m=2

2m-5n=-11
m=2

2*2-5n=-11
m=2

4-5n=-11
m=2

-5n=-11-4
m=2

-5n=-15 /:(-5)
m=2

n=3
m=2

d) 4a-2=b
3a+7b=1,5

b=4a-2
3a+7(4a-2)=1,5

b=4a-2
3a+28a-14=1,5

b=4a-2
3a+28a=1,5+14

b=4a-2
31a=15,5/:31

b=4a-2
a=0,5

b=4*0,5-2
a=0,5

b=0
a=0,5

f)6x-3y=9
x+5y=-9,5

6x-3y=9
x=-9,5-5y

6(-9,5-5y)-3y=9
x=-9,5-5y

-57-30y-3y=9
x=-9,5-5y

-30y-3y=9+57
x=-9,5-5y

-33y=66 /:(-33)
x=-9,5-5y

y=2
x=-9,5-5y

y=2
x=-9,5-5*2

y=2
x=-9,5-10

y=2
x=-19,5





2009-12-15T19:33:36+01:00
A) 3x=12
x-y=5

3x=12/:3
x-y=5

x=4
x-y=5

x=4
4-y=5

x=4
y=-1

b) 5y=2/:5
x+y=2i2/5

y=2/5
x+y=2 2/5

y=2/5
x+2/5=2 2/5

y=2/5
x=2 2/5-2/5

y=2/5
x=2

c) 3m+n=9 /*5
2m-5n=-11

15m+5n=45
2m-5n=-11

17m=34 /:17
m=2

2m-5n=-11
m=2

2*2-5n=-11
m=2

4-5n=-11
m=2

-5n=-11-4
m=2

-5n=-15 /:(-5)
m=2

n=3
m=2

d) 4a-2=b
3a+7b=1,5

b=4a-2
3a+7(4a-2)=1,5

b=4a-2
3a+28a-14=1,5

b=4a-2
3a+28a=1,5+14

b=4a-2
31a=15,5/:31

b=4a-2
a=0,5

b=4*0,5-2
a=0,5

b=0
a=0,5

f)6x-3y=9
x+5y=-9,5

6x-3y=9
x=-9,5-5y

6(-9,5-5y)-3y=9
x=-9,5-5y

-57-30y-3y=9
x=-9,5-5y

-30y-3y=9+57
x=-9,5-5y

-33y=66 /:(-33)
x=-9,5-5y

y=2
x=-9,5-5y

y=2
x=-9,5-5*2

y=2
x=-9,5-10

y=2
x=-19,5